Molecular mechanisms involving sigma receptor–mediated induction of MCP-1: implication for increased monocyte transmigration - Yao, Honghong (American Society of Hematology, 2010)
Cocaine abuse hastens the neurodegeneration often associated with advanced HIV-1 infection. The mechanisms, in part, revolve around the neuroinflammatory processes mediated by the chemokine monocyte chemotactic protein-1 (MCP-1/CCL2). Understanding factors that modulate MCP-1 and, in turn, facilitate monocyte extravasation in the brain is thus of paramount importance. We now demonstrate that cocaine induces MCP-1 in rodent microglia through translocation of the sigma receptor to the lipid raft microdomains of the plasma membrane. Sequential activation of Src, mitogen-activated protein kinases (MAPKs), and phosphatidylinositol-3′ kinase (PI3K)/Akt and nuclear factor κB (NF-κB) pathways resulted in increased MCP-1 expression. Furthermore, conditioned media from cocaine-exposed microglia increased monocyte transmigration, and thus was blocked by antagonists for CCR2 or sigma receptor. These findings were corroborated by demonstrating increased monocyte transmigration in mice exposed to cocaine, which was attenuated by pretreatment of mice with the sigma receptor antagonist. Interestingly, cocaine-mediated transmigratory effects were not observed in CCR2 knockout mice. We conclude that cocaine-mediated induction of MCP-1 accelerates monocyte extravasation across the endothelium. Understanding the regulation of MCP-1 expression and functional changes by cocaine/sigma receptor system may provide insights into the development of potential therapeutic targets for HIV-1–associated neurocognitive disorders.